Strategies for Improving Indigenous Financial Literacy in Schools - Bin-Sallik, Maryann; Adams, Isabella; Vemuri, Siva Ram (The Australian Journal of Indigenous Education, 2004)
Abstract The Indigenous Australian population is not only considerably younger than the non-Indigenous population but is also on the rise. The challenge for many is to provide the kind of education that equips young Indigenous Australians with the necessary skills for managing their money. This challenge is further compounded, as the adult Indigenous population is not well versed in money management. This paper examines some of the strategies that are needed to improve Indigenous financial literacy in schools.